The role of RPA/Low-Code in process transformation. How well-implemented RPA/Low-Code projects can help transform a company´s process development? - Marques, Diogo Vargas (2023)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics